Correlation of competitive market structure and innovative activity of oil and fat companies - N. V. Orlova (Ринкова економіка: сучасна теорія і практика управління, 2017)
The article considers the current state of the oil and fat industry from the standpoint of its competitive structure, and identifies the main problems of its development in Ukraine. It was established that the fat-oil sub-complex is one of the most promising sectors of the national economy. The sub-complex fully meets the needs of the domestic market in oily products and allows exporting products to foreign markets. In addition, its role is important in shaping the consumption fund, solving the problems of internal food security, ensuring currency and tax revenues, as well as solving a number of social problems through the creation of a significant number of jobs in the fat and oil subcomplex and related industries. The industry has a high level of monopolization. Most enterprises are part of large corporate agribusiness formations, agroholdings and multinational companies. Monopolists can dictate their conditions both in the market of raw materials and in the market of finished products by consolidating their companies. It allows them to regulate profitability of production and to reduce the influence of competitors. Competition in the global markets of vegetable oil has escalated in recent years. A complex of problems, the solution of which will largely determine the development of the oil and fat industry in the long term, is connected both with the increase in the raw material base and the expansion of various types of oilseeds production, and with the modernization and expansion of production capacities on the basis of scientific and technological progress, the development of a new innovation-investment strategy of forming industry competitive advantages of oil and fat companies by improving competition policy.